Use of the over-the-scope-clip (OTSC) in non-variceal upper gastrointestinal bleeding in patients with severe cardiovascular comorbidities: a retrospective study - Wedi, Edris; von Renteln, Daniel; Gonzalez, Susana; Tkachenko, Olena; Jung, Carlo; Orkut, Sinan; Roth, Victor; Tumay, Selin; Hochberger, Juergen (Endoscopy International Open, 2017)
Introduction The over-the-scope-clip (OTSC) can potentially overcome limitations of standard clips and achieve more efficient and reliable hemostasis. Data on OTSC use for non-variceal upper gastrointestinal bleeding (NVUGIB) in patients with cardiovascular comorbidities are currently limited. Patients and methods We prospectively collected and retrospectively analyzed our database from February 2009 to September 2015 from all patients who underwent emergency endoscopy for high-risk NVUGIB in 2 academic centers and were treated with OTSC as first-line (n = 81) or second-line therapy (n = 19). Results One hundred patients mean age 72 (range 27 – 97 years) were included in this study. Fifty-one percent (n = 51) had severe cardiovascular co-morbidity (ischemic heart disease, congestive heart failure, hypertension, valvular heart disease, peripheral arterial occlusive disease and atrial fibrillation) and 73 % (n = 73) were on antiplatelet or/and anticoagulation therapy. The median size of the treated ulcers was 3 cm (range 1 – 5 cm). In 94 % (n = 94) primary hemostasis with OTSC was achieved. Clinical long-term success during a mean 6-month follow-up without rebleeding was 86 % (n = 86). Conclusions In this cohort OTSC was demonstrated to be a safe and effective first- or second-line treatment for NVUGIB in high-risk patients with cardiovascular disease and complex, large ulcers. Meeting presentations: Annual Meeting of the German Society of Endoscopy (DEGBV) in Mannheim, Germany, March 17th–19th, 2016 and DDW 2016 in San Diego, United States